The Dying Sahara. US Imperialism and Terror in Africa by Jeremy Keenan - El Alaoui, Ayoub (Afrika Tanulmányok / Hungarian Journal of African Studies, 2024)
Jeremy Keenan: The Dying Sahara. US Imperialism and Terror in Africa. Pluto Press, 352 p. Review Bb: Ayoub El Alaoui